The End of Art: A Hegelian Conception of the Postmodern Paradigm - Peel, Lishai (The Oracle, 2021)
This essay will use the Hegelian understanding of dialectical history as a model for the history of art. Through this model it will be shown that postmodern art is the actualization of artistic freedom whereby greater artistic autonomy has enabled artists to conceptualize, philosophize and theorize about the world around them to a much greater extent than at any other point in history. The result of this artistic autonomy is that art has now taken on a dual identity of both art and philosophy. Consequently, art, as it is historically known, is a thing of the past.